Pemberdayaan UMKM Dengan Pelatihan Branding Dan Penguatan Pemasaran Produk Menggunakan Strategi Branding Di Kebraon - Setiawan, Muhammad Ricky; Eko Purwanto (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the economy in Indonesia. This is due to the existence of MSMEs jobs, poverty eradication, contributions to innovation and the GDP of Indonesia can be created. The era of the Industrial Revolution 4.0 concerning the development of MSMEs in Indonesia, the owners and or managers of the MSMEs are required to compete. The village in Kebraon became a suitable choice as a place to carry out service activities to the community, MSMEs perpetrators and the community around have branding problems products. To overcome these problems students planned programmes related to socialization about branding and logo consultation with MSMEs and the dissemination of brochures to MSMEs actors and the society in kebraon. The purpose of this community's dedication is to help develop and enhance branding and product logo knowledge to local MSMEs. The method used is with education, support to the perpetrators of MSMEs and the community around in Kebraon. The results of the activities that have been carried out through community dedication to MSMEs and local communities, contribute in improving the understanding and skills of small business operators. With the knowledge given, MSMEs can strengthen their product identity and improve branding management, build community brand awareness to products, open up opportunities for sustainable business growth.